How to develop a sensor system to assess the potential risk of running-related injury of the foot and ankle? - Hashizume, S.; Hobara, H.; Kobayashi, Y. (Clinical Research of Foot and Ankle, 2017)
In summary, this letter discussed the development of a sensor system for assessment of the potential risk of running-related injury of the foot and ankle. The following two steps are thought to be required: 1) first, the potential risk of each running-related injury of the foot and ankle should be accurately assessed by computation of the forces applied to corresponding injured regions, and 2) second, the algorithm to estimate the forces applied to injured regions from sensor data should be then developed. Compact and inexpensive sensors with the developed algorithm may be used at training fields by runners themselves. These two steps can be resolved by using the inverse and forward dynamics techniques, and the vector-based pattern recognition techniques, respectively.